Two Stay Two Stray Model in Mastering Arabic Vocabulary - Shofa, Nur Azkia; R, Mantasiah; Bachtiar, Fauziah (Universitas Negeri Makassar, 2024)
Abstract. This research is a type of Quasy Experimental Design which aims to determine the effectiveness of Two Stay Two Stray learning model in mastering Arabic vocabulary of 8th grade students of MTs Muhammmadiyah Tanetea Jeneponto. There are two variables in this study, namely the independent variable and the dependent variable. The independent variable in this study is the use of Two Stay Two Stray learning model, while the dependent variable is the mastery of Arabic vocabulary. The population in this study were all students of class VIII MTs Muhammadiyah Tanetea Jeneponto, which amounted to 40 students. The sample in the study was all VIII grade students of MTs Muhammadiyah Tanetea Jeneponto as many as 40 students consisting of class VIII.B as an experimental class with a total of 20 students and class VIII.A as a control class with a total of 20 students selected using total sampling technique. Data on the results of this study were obtained by giving a written pre-test and post-test on the material